Peluang Dan Tantangan Transformasi IAIN Surakarta Menjadi UIN Raden Mas Said Surakarta - Firda Imah Suryani; Deny Marita Wijayanti (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The transformation of Islamic State Institute (IAIN) Surakarta into Islamic State University (UIN) Raden Mas Said Surakarta go through a long process as well as created opportunities and challenges to be faced. The process formed into the education system and the development of educational institutions and the development of Islamic higher education institutions. Various strategies to develop opportunities also contribute to support towards further development. This study aims to understand and find out the opportunities and challenges in supporting development after changing the status of IAIN Surakarta to UIN Raden Mas Said Surakarta as well as strategies carried out in overcoming the existing challenges. The research method uses a qualitative approach with SWOT technique. Data were collected through interviews with the chancellor, vice iii chancellor for student affairs, lecturers, and student affairs as well as observations. There are a number of opportunities and challenges from the transformation process of UIN Raden Mas Said Surakarta. These opportunities and challenges need to be addressed to improve the quality of UIN Raden Mas Said Surakarta after the transformation.